1997
DOI: 10.1093/emboj/16.11.3219
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian homologues of the Polycomb-group gene Enhancer of zeste mediate gene silencing in Drosophila heterochromatin and at S.cerevisiae telomeres

Abstract: Gene silencing is required to stably maintain distinct patterns of gene expression during eukaryotic development and has been correlated with the induction of chromatin domains that restrict gene activity. We describe the isolation of human (EZH2) and mouse (Ezh1) homologues of the Drosophila Polycomb-group (Pc-G) gene Enhancer of zeste [E(z)], a crucial regulator of homeotic gene expression implicated in the assembly of repressive protein complexes in chromatin. Mammalian homologues of E(z) are encoded by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
233
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(245 citation statements)
references
References 84 publications
(175 reference statements)
11
233
0
Order By: Relevance
“…In mammals, two E(z)-related genes have been isolated, Ezh1 and Ezh2. Ezh1 expression is prevalent in the adult, whereas Ezh2 is expressed during embryonic development (Laible et al, 1997). Consistent with this observation, Ezh2 is required for early mouse development.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In mammals, two E(z)-related genes have been isolated, Ezh1 and Ezh2. Ezh1 expression is prevalent in the adult, whereas Ezh2 is expressed during embryonic development (Laible et al, 1997). Consistent with this observation, Ezh2 is required for early mouse development.…”
Section: Introductionsupporting
confidence: 71%
“…Ezh2 À null mouse embryos die during the transition from pre-to post-implantation development (O'Carroll et al, 2001). The mRNA expression of Ezh2 has been identified in whole mouse embryos at day E9.5 and in the fetal liver, brain and skeletal muscles at day E13 or day E17 (Laible et al, 1997). Studies also suggested that Ezh2-induced H3K27me3 might be an important epigenetic marker for evaluating the developmental potential of cloned embryos (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SirT1 may function analogously to HDAC1 or spSir2, but with respect to H1-K26. Moreover, a connection between SirT1 and Ezh2 was revealed by their independent participation in PEV (Laible et al 1997;Rosenberg and Parkhurst 2002). Following this hunch, we found that SirT1 was indeed associated, specifically with PRC4 (Figs.…”
Section: Inheritance Of Repressive Methyl-lysine Marks In Histones 175mentioning
confidence: 54%
“…In most cases the SET domain is associated with lysine-specific methyltransferase activity. Overexpression of Ezh2 was known to enhance PEV (Laible et al 1997). We set out to examine whether this Ezh2-associated gene repression correlates with its putative HKMT activity.…”
Section: Ezh2mentioning
confidence: 99%
“…EZH2 encodes the EZH2 protein, which is a known repressor of transcription. 67 EZH2 causes generalised reduction in transcription in PC by increasing histone deacetylation via histone deacetylase-2. Varambally et al 12 found that EZH2 mRNA and protein are significantly increased in malignant PC compared to the benign prostate, and higher concentrations of EZH2 mRNA and protein in clinically localised PC predicts a poor prognosis.…”
Section: Ezh2 Polycomb Oncogenementioning
confidence: 99%